Influence of parameters in the plasma dynamic synthesis process on ultradispersed zinc oxide; 6th International Congress on Energy Fluxes and Radiation Effects; 3rd International Conference on New Materials and High Technologies (3rd NMHT), November 2018 - Tsimmerman (Cimmerman) A. I. Aleksandr Igorevich (2018, 2018)
Title screen